ANALYSIS OF BASIC SKILLS OF SEPAK SILA IN SEPAK TAKRAW GAMES - Ibrahim, Muhammad Bagus Ragil; Topo Yono (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to determine the skill level of basic sepak takraw techniques among sepak takraw athletes at SD Negeri Gunungmalang 03. The research employs a descriptive quantitative method. The participants consist of five students enrolled in the school's sepak takraw extracurricular program, selected based on availability during the test. The sampling method used is purposive sampling. Data collection was conducted through a football skills test, assessing the frequency of football skills performed within one minute over three trials. Data analysis was carried out using descriptive statistics in the form of percentages. The results indicate that the majority of participants demonstrated a "very good" skill level (60%) and a "good" skill level (40%), with no participants falling into the categories of moderate, poor, or very poor. These findings suggest that the sepak takraw extracurricular program at SD Negeri Gunungmalang 03 has positively contributed to improving the students' basic technical skills. The study concludes that structured and consistent training can improve sepak sila skills, which is a crucial component of sepak takraw. Therefore, greater attention should be given to the intensity and quality of training to ensure continuous skill development among athletes.